2007
DOI: 10.1016/j.ecolecon.2006.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Protected areas, wildlife conservation, and local welfare

Abstract: 2 Protected areas, wildlife conservation and local welfare AbstractThe establishment and expansion of protected areas in Africa have been motivated by the aspiration of increased wildlife abundance. During the past decades, however, this practise has been subject to a massive debate. While some claim that protected areas have failed in preserving African wildlife, others claim that existing protected areas are successful. This paper adds to this debate by presenting a bio-economic analysis of protected area ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
0
18
1
2
Order By: Relevance
“…This finding is in line with modeling results from Skonhoft [4] who stated that wildlife conservation can work directly against the interests of local people. Johannesen [8] also reported that expansion of protected areas may reduce welfare of the local people. Our findings extend this literature by adding that even with the argument of wildlife being more adapted to semi-arid savannas than introduced livestock [41], income from wildlife can only provide insurance value to local people during dry years in the absence of irrigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with modeling results from Skonhoft [4] who stated that wildlife conservation can work directly against the interests of local people. Johannesen [8] also reported that expansion of protected areas may reduce welfare of the local people. Our findings extend this literature by adding that even with the argument of wildlife being more adapted to semi-arid savannas than introduced livestock [41], income from wildlife can only provide insurance value to local people during dry years in the absence of irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that when people are taxed (either physically or financially) and do not benefit, they see a burden. For these and other reasons, protected areas, especially in Africa, have often operated against the economic interests of local communities, and persistent poaching pressure has led to a growing recognition that this 'fences and fines' approach has in many cases failed to achieve its objective of preserving wildlife [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Celles-ci ont alors perdu leurs terres de culture et de pâture au profit de la création d'aires protégées, et les lois anti-braconnages ont transformé leur chasse de subsistance en crime contre les animaux (Skonhoft, 1998). Cette attitude a été source d'aggravation de la pauvreté au sein des populations locales, et malgré les répressions, elle a engendré l'émergence d'un braconnage intensif de la part de ces dernières dans le cas des aires protégées de faune sauvage (Haule et al, 2002 ;Johannesen, 2007).…”
Section: Résuméunclassified
“…Local communities traditionally perceive protected areas as a burden due to their primary mission of protecting natural resources against use (Almudi and Kalikoski 2010;Salafsky 2011). Protected areas are blamed for downsides in socio-economic relationships (e.g., autonomy freedom, traditional use, local economy) generated by restricted access to resources in addition to the impact of protected areas on surrounding lands (Saberwal et al 1994;Johannesen 2007;Monney et al 2010). Both the factors are disturbing (e.g., lack of alternative resources outside of reserves, risk of damage on crop, livestock, and human injuries/lives by animals crossing the reserve border), and causing suffering of significant opportunity costs (James et al 1999;Weladji and Tchamba 2003;Kideghesho and Mtoni 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both the factors are disturbing (e.g., lack of alternative resources outside of reserves, risk of damage on crop, livestock, and human injuries/lives by animals crossing the reserve border), and causing suffering of significant opportunity costs (James et al 1999;Weladji and Tchamba 2003;Kideghesho and Mtoni 2008). Ultimately, the achievement of conservation goals is reduced, or at the very least, delayed (Johannesen 2007).…”
Section: Introductionmentioning
confidence: 99%